Retreating Academics: Creating Spaces for the Scholarship of Teaching and Learning: Creating Spaces for the Scholarship of Teaching and Learning - Southwood, Sue (Critical Studies in Teaching and Learning, 2023)
Recognising the struggles many academics experience around academic writing, this paper explores particular spaces created to support academic engagement in the scholarship of teaching and learning: the space of writing retreats. The metaphor of ‘tapestry’ is used to capture the development of a complex conceptual image of the writing retreats. A metatheoretical framework - a matrix built from the ‘warp’ and ‘weft’ of spatiality and sociality - supports the development of a pedagogical picture of presence. Analysis of qualitative data, generated through questionnaires and informal group discussions, led to the identification of dimensional ‘threads’, considered as enabling conditions, for scholarly engagement. Such dimensions speak to spaces not only within (personal) and between people (interpersonal), but also spaces beyond (extrapersonal).